Dietary fibre: influence on body weight, glycemic control and plasma cholesterol profile Fibra dietética: influencia sobre el peso corporal, el control glicémico y el perfil del colesterol plasmático - N. Babio; R. Balanza; J. Basulto; M. Bulló; J. Salas-Salvadó (Nutrición Hospitalaria, 2010)
There have been several studies on the effects of dietary fibre on the metabolism. Epidemiologic studies have consistently reported an inverse relationship between dietary fibre and type 2 diabetes mellitus or cardiovascular mortality. This review focuses on observational and experimental studies that examine the effect of different types and sources of dietary fibre on body weight, glucose metabolism and lipid profile. From the available evidence, we conclude that clinical studies consistently show that the intake of viscous dietary fibre decreases the low density lipoprotein cholesterol and postprandial glucose levels, and induces short term satiety. However, few clinical trials have demonstrated that the intake of dietary fibre has a positive effect on the control of diabetes and body weight. Existen diversos estudios que han evaluado el efecto del consumo de fibra dietética sobre el metabolismo. Diversos estudios epidemiológicos observaron una relación inversa entre la fibra dietética y la diabetes mellitas tipo 2 o la mortalidad cardiovascular. Esta revisión se basa sobre estudios observacionales y experimentales que han valorado los efectos de diferentes tipos y fuentes de fibra dietética sobre el peso corporal, el metabolismo de la glucosa y el perfil lipídico. De la evidencia disponible, concluimos que los estudios clínicos consistentemente muestran que la ingesta de alimentos fuentes de fibra viscosa disminuye el colesterol de las lipoproteínas de baja densidad y los niveles de glucosa postprandial e induce la saciedad a corto plazo. Sin embargo, pocos ensayos clínicos han demostrado un efecto positivo sobre el control de la diabetes y el peso corporal.